Investigation of Teacher-Pupils Relationships with the Focus Group Method - Αναγνωστοπούλου Μαρία; Σουσαμίδου Αικατερίνη (Education Sciences, 2021)
The aimpurpose of this study was to analyze the interpersonal teacher-pupil relationships, from the point of view of primary school teachers, using the qualitative method of focus group. The study involved 32 elementary school teachers answering questions about definition and importance of interpersonal teacher-pupils relationships, teachers’ characteristics that influence these relationships and techniques for improving relationships, expressing their general and personal opinions about these issues. The analysis of their answers revealed that teachers consider that good interpersonal relationships are necessary in a classroom because they contribute to the pedagogical climate, pupils’ learning and motivation. They believe that pupils prefer a fair teacher, consistent, accessible, communicative, humorous, and decisive, well-educated, young and mostly female. Play, discussion and educational programs that integrate art into the learning process are mentioned as techniques which could improve interpersonal relationships. The results could be useful to training programs ofstudents-teachers to be and in-service teachers.